Outcrop gamma-ray spectrometry: Applications to the Sinemurian–Pliensbachian organic-rich facies of the Lusitanian Basin (Portugal) - Correia, G. G.; Duarte, L. V.; Pereira, A.; Silva, R. L. (Journal of Iberian Geology, 2012)
This work provides detailed information of outcrop gamma-ray logging from the Sinemurian–Pliensbachian organic-rich units (Água de Madeiros and Vale das Fontes formations) of the Lusitanian Basin, which are recognized as one of the most important potential oil source rocks interval of Portugal. The study included total and spectral gamma-ray measurements in outcrop and laboratory, Total Organic Carbon (TOC) content and whole-rock mineralogical characterization by X-ray diffraction, carried out in the two most important outcrop areas of the Western Lusitanian Basin (S. Pedro de Moel and Peniche). The outcrop data was compared with subsurface information. The results show high variability of the gamma radiation (26 to 210 cps) and radioactive elements associated with the lithological, mineralogical and geochemical differences. The TOC data yielded the organic matter enrichment of both formations, where the highest values are observed in the Água de Madeiros Formation (maximum=20.4%). The highest U concentration (11 ppm) is consistent with the highest Total Organic Carbon peak mainly supported by the precipitation of authigenic U (10 ppm). The majority of the analysed samples show an obvious authigenic U enrichment, especially in the Água de Madeiros Formation where it represents the main component of the total U content. A highly significant U/TOC correlation (r up to 0.87) with a low ratio (0.3–0.7 ppm/wt.%TOC) was obtained, confirming that U content can be used as a proxy for organic richness in the studied depositional system. The gamma-ray tool was also useful in the identification of 2nd order Transgressive–Regressive facies cycles (and maximum flooding surfaces) and in the correlation between outcrop and subsurface data.